Turning microscopy in the medical curriculum digital: Experiences from the faculty of health and medical sciences at University of Copenhagen - Ben Vainer; Niels Werner Mortensen; Steen Seier Poulsen; Allan Have Sørensen; Jørgen Olsen; Hans Henrik Saxild; Flemming Fryd Johansen (Elsevier, 2017)
Familiarity with the structure and composition of normal tissue and an understanding of the changes that occur during disease is pivotal to the study of the human body. For decades, microscope slides have been central to teaching pathology in medical courses and related subjects at the University of Copenhagen. Students had to learn how to use a microscope and envisage three-dimensional processes that occur in the body from two-dimensional glass slides. Here, we describe how a PathXL virtual microscopy system for teaching pathology and histology at the Faculty has recently been implemented, from an administrative, an economic, and a teaching perspective. This fully automatic digital microscopy system has been received positively by both teachers and students, and a decision was made to convert all courses involving microscopy to the virtual microscopy format. As a result, conventional analog microscopy will be phased out from the fall of 2016.